2014
DOI: 10.14348/molcells.2014.2371
|View full text |Cite
|
Sign up to set email alerts
|

SIFamide and SIFamide Receptor Define a Novel Neuropeptide Signaling to Promote Sleep in Drosophila

Abstract: SIFamide receptor (SIFR) is a Drosophila G protein-coupled receptor for the neuropeptide SIFamide (SIFa). Although the sequence and spatial expression of SIFa are evolutionarily conserved among insect species, the physiological function of SIFa/SIFR signaling remains elusive. Here, we provide genetic evidence that SIFa and SIFR promote sleep in Drosophila. Either genetic ablation of SIFa-expressing neurons in the pars intercerebralis (PI) or pan-neuronal depletion of SIFa expression shortened baseline sleep an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 37 publications
(45 reference statements)
2
57
0
Order By: Relevance
“…SIFamide is a well conserved neuropeptide in insects and crustaceans79. In insects, SIFamide has been proven to have a role in sexual behaviour80 and promote sleep in Drosophila melanogaster 81.…”
Section: Discussionmentioning
confidence: 99%
“…SIFamide is a well conserved neuropeptide in insects and crustaceans79. In insects, SIFamide has been proven to have a role in sexual behaviour80 and promote sleep in Drosophila melanogaster 81.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the involvement of dopaminergic, GABAergic, and peptidergic neurons are well characterized142643444546. In particular, Drosophila sleep/wake behaviors is modified by several neuropeptides, including the short neuropeptide F, neuropeptide F, SIFamide, and Ion transport peptide4748495051. Previous studies have revealed that Ap is necessary for expression of neuropeptides [FMRFamide and Leucokinin (Lk)] in the central nervous system910.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the neuropeptide pigment dispersing factor (PDF) is involved in both arousal (Parisky et al, 2008; Sheeba et al, 2008) and clock output mechanisms (Renn et al, 1999). Recent work has shown sleep promoting roles of SIFamide (Park et al, 2014) and sNPF (Shang et al, 2013) secreted from pars intercerebralis and small ventrolateral clock cells, respectively. The precise role of sNPF, which, Like FMRFa, is a member of the FaRP family (Nassel and Winther, 2010), remains uncertain since it has also been reported to serve a wake-promoting role (Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%